Bauran Pemasaran terhadap Loyalitas Pelanggan Kedai Kopi di Bandung - Erlina, Erlina; Hermawan, Daniel (APTISI Transactions on Management (ATM), 2021)
Coffee shop business growing rapidly in Bandung. Not just enjoying a cup of coffee, coffee shops are now transformed into places to socialize and gather together with friends and relatives. This trend makes existing coffee shops compete with one another by providing differentiation in product, price, place, promotion, service, atmosphere, and presentation process. This research tries to explore the marketing mix at coffee shop in Bandung and its effect on customer loyalty. With quantitative research methods taken from 80 respondents, it is known that the physical evidence factor is the main factor, on the other hand the price factor is the lowest factor that has impact on customer loyalty. This research underlines the importance of the components of the marketing mix in order to increase customer loyalty in the coffee shop business.